Physical factors that differentiate body kinematics between treadmill and overground walking - Jung, Mingi; Koo, Seungbum (Frontiers in Bioengineering and Biotechnology, 2022)
Treadmills are widely used in rehabilitation and gait analysis. However, previous studies have reported differences in terms of kinematics and kinetics between treadmill and overground walking due to physical and psychological factors. The aim of this study was to analyze gait differences due to only the physical factors of treadmill walking. Walking motions of a male participant were captured at 0.63, 1.05, 1.33, and 3.91 m/s. A gait controller of a virtual subject (63 kg) was trained for ground walking at each walking speed via a reinforcement learning method. Additionally, the gait controllers of virtual subjects with different body masses of 47, 79, and 94 kg were trained for ground walking at 1.05 m/s. The gait controllers and virtual subjects were tested for treadmill walking, and their lower-limb joint kinematics were compared with those for ground walking. Treadmill conditions of maximum allowable belt force and feedback control frequency of belt speed were set between 100 and 500 N and between 10 and 50 Hz, respectively. The lower-limb kinematics were identical between the two conditions regardless of the body mass and walking speed when the belt could provide a constant speed regardless of external perturbation in the ideal treadmill. However, kinematic differences were observed when simulation was performed on a non-ideal treadmill with a relatively low belt force and control frequency of belt speed. The root-mean-square differences of the hip, knee, and ankle flexion angles between treadmill and overground running at 3.91 m/s increased by 3.76°, 3.73°, and 4.91°, respectively, when the maximum belt force and control frequency decreased from infinity to 100 N and 10 Hz, respectively. At a maximum belt force exceeding 400 N or a control frequency exceeding 25 Hz, the root-mean-square difference of the joint kinematics was less than 3° for all body masses and walking speeds. Virtual subjects walking on non-ideal treadmills showed different joint kinematics from ground walking. The study identified physical factors that differentiate treadmill walking from overground walking, and suggested the belt forces and control frequencies of a treadmill to achieve the desired limit of kinematic differences.